2013
DOI: 10.1254/jphs.12243fp
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Inhibits Osteoclastogenesis Through Prevention of RANKL-Induced ROS Production by Nrf2-Mediated Up-regulation of Phase II Antioxidant Enzymes

Abstract: Abstract. Osteoclasts (OCLs) are multinucleated bone-resorbing cells that are differentiated by stimulation with receptor activator of nuclear factor kappa-B ligand (RANKL) and macrophage colony-stimulating factor. We recently demonstrated that regulation of heme-oxygenase 1 (HO-1), a stress-induced cytoprotective enzyme, also functions in OCL differentiation. In this study, we investigated effects of fisetin, a natural bioactive flavonoid that has been reported to induce HO-1 expression, on the differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Previous studies have reported that the intracellular ROS level increases during RANKL-induced osteoclast differentiation, and this ROS generation can be attenuated by several antioxidants, including curcumin and fisetin [29,30]. Our previous study also showed that the intracellular ROS level in RANKL-stimulated Raw 264.7 cells increased to its largest value within two days and then declined [28].…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies have reported that the intracellular ROS level increases during RANKL-induced osteoclast differentiation, and this ROS generation can be attenuated by several antioxidants, including curcumin and fisetin [29,30]. Our previous study also showed that the intracellular ROS level in RANKL-stimulated Raw 264.7 cells increased to its largest value within two days and then declined [28].…”
Section: Resultsmentioning
confidence: 71%
“…Treatment with genistein reduced the number of multinucleated TRAP-positive cells and TRAP activity in a dose-dependent manner (Figure 2B,C). The inhibitory effects of natural flavonoids, such as luteolin [24], baicalein [25], resveratrol [26], epigallocatechin-3-gallate [27], scopoletin [28], curcumin [29] and fisetin [30], as potent antioxidants on osteoclast differentiation from osteoclastic precursors through controlling ROS generation, have also been reported. The suppressive effect on osteoclastogenesis via attenuating ROS production in RANKL-treated RAW 264.7 cells was observed in luteolin, which showed potent cellular antioxidant activity in rat C6 astroglioma cells [22,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…siRNA experiments in OCLs were performed as described previously48. The target sequence of murine Rab27A siRNA was: GGACUUAAUCAUCTAAGAGAAUGGAA (Rab27A siRNA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several researchers worked on the antioxidant potential of fisetin by performing various tests. [18][19][20] Wherein Phenolic hydroxyl groups are prone to donate a hydrogen atom to free radicals and extend conjugated aromatic system to delocalize an unpaired electron. 21 DPPH radical scavenging activity guided isolation of acetone extract of E. indica yielded a flavonol compound, i.e.…”
Section: Antioxidant Activity Of Fisetinmentioning
confidence: 99%